Cancer principles and practice of oncology - DeVita, Vincent T; Hellman, Samuel; Rosenberg, Steven A (Lippincott Williams & Wilkins, 2001)
Yale Univ., New Haven, CT. Brandon/Hill Medical List minimal-core and first-purchase selection (#360). Classic and comprehensive text describes the science underlying recent clinical developments as well as complete information to aid the clinician in clinical care. CD-ROM contains complete text and additional illustrations. Two-volume set also available.
Keywords: Neoplasms; nádory; onkologie